Meningkatkan Budaya Literasi Mahasiswa dalam Pembelajaran Pendidikan Islam Berbasis Teknologi - Alrasi, Fitri; Azwar, Azwar; Akhir, Nur Afzan Binti Md (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2023)
Religious learning innovations in the era of society 5.0, education providers in general, and providers of Islamic Religious Education in state universities must be more digital, think creatively, and be more imaginative and dynamic because almost all educational activities rely on advances in technology and information. Compete in the use of technology and information in learning activities, including learning Islamic Religious Education in State Universities. Revitalization of the learning system, educational units, elements of students, educators, and educational staff all play a role in the effectiveness of Islamic Religious Education learning, such as the idea of ​​Islamic religious education. Descriptive and argumentative analysis was used in this research. The research results show that the Islamic Religious Education learning process is needed to compete in the use of technology and information in learning activities. An educator or lecturer who plays a leadership role in the field of education must be able to utilize digital learning applications such as e-learning. Zoom, Google Meet, Discord, Edmodo, Kahoot, and home learning, as well as the selection and application of Islamic Religious Education learning methodologies in state universities, are more harmonious and capable of producing a generation of superior and capable Muslims. Islamic religious learning innovations in public universities using digital literacy must be able to prepare students who are religiously and scientifically competent. Students will have competitiveness in the world of work if they have the capital to master digitalization in transferring their knowledge to society.